Impact Of Social Awareness Of Students’ Emotional Competency - Zihao, Liu; Kee, Chng Lay (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose: The primary aim of this study is to examine the association between social awareness  and the emotional competence of students. Self-awareness and social awareness are the  independent variables of the study, while emotional competency is the dependent construct.  Additionally, the research investigates the mediating impact of cognitive appraisal and self efficacy, as well as the moderating influence of personal well-being. The study is carried out  in relation to the educational system of China. Students presently enrolled in institutions of  higher education constituted the target population of the research.  Method: The present investigation utilizes a quantitative methodology. The data was gathered  through the administration of a survey questionnaire comprising closed-ended questions. The  statistical software packages AMOS and SPSS were utilized in the analysis of the data for this  study.  Findings: The results of the study revealed a significant correlation between SA and both SAW  and SE. The impact of CA on the efficacy of SA and SAW is also significant. A significant  association exists between EC and the variables SA, SAW, and CA. However, the relationship  between EC and SE is insignificant. While CA's impact is relatively insignificant, SE assumes  a substantial role in mediating the situation. Additionally, it was ascertained that the moderating  effect of PWB had a significant statistical impact.  Conclusion and Implications: The findings contribute to practical applications and theoretical  frameworks both. In addition to identifying potential avenues for future research, the study has  assessed its own limitations.
Keywords: cognitive appraisal; self-efficacy; social awareness; self-awareness; emotional competency; personal well-being; China